Dependency, (non)liability and austerity news frames of bailout Greece - Doudaki, Vaia; Boubouka, Angeliki; Spyridou, Lia Paschalia; Tzalavras, Christos (My University, 2016)
Instructed theoretically by the critical discussion on the media’s alignment with the institutions of power in societies, this study examines how the Greek legacy press framed the discussion over the crisis, by focusing on the bailout agreements Greece signed with the troika during the period 2010–2012. The analysis, following a three-step process in frames’ detection, focuses on the associations of actors and their responsibility, causes, solutions and effects of the crisis and the bailouts, as appearing in the news texts studied, and reveals a de-contexualised neoliberal discourse articulated through three distinct frames: the dependency, the (non)liability and the austerity frame. The representations of the financial crisis in the newspapers studied largely echo the neoliberal voices and strengthen the hegemonic discourse over the necessity and inescapability of the bailout policies, feeding the ‘masterframe’ of the neoliberal vision of the crisis.
Keywords: Bailout; Economic crisis; Greece; News framing; Frames